Optimisme dan Pesimisme serta Hubungannya dengan Prestasi Akademik dalam Sepak Bola di Kalangan Mahasiswa Fakultas Pendidikan Jasmani dan Ilmu Olahraga Hussein Rashid Ghyaidh - Hussein Rashid Ghyaidh (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. The present study aims to assess the levels of optimism and pessimism and their relationship with academic achievement among students of the College of Physical Education and Sports Sciences at Al-Qadisiyah University. It further seeks to determine whether there are statistically significant differences in these relationships based on gender (male/female) and type of academic achievement (theoretical/practical). Materials and methods. The study employed a descriptive research design using survey and correlational approaches. The research population consisted of 212 first-year students enrolled at the College of Physical Education and Sports Sciences, Al-Qadisiyah University, during the academic year under study. A sample representing 85% of the total population (180 students: 154 males and 26 females) was selected. Data were collected through validated psychological scales assessing optimism and pessimism, in addition to records of students’ academic performance. Appropriate statistical techniques including measures of central tendency, correlation coefficients, and tests for gender and academic achievement differences were applied to analyze the data. Results. The findings revealed a generally high level of optimism and pessimism among the participating students. A statistically significant positive correlation was found between optimism and pessimism, indicating that the two constructs coexist in a balanced psychological framework among the students. However, the analysis demonstrated no statistically significant differences in the correlation between optimism/pessimism and academic achievement when compared across gender (male/female) or academic domains (theoretical/practical). Conclusions. The results suggest that students exhibit a balanced psychological disposition characterized by both optimism and pessimism. While these traits are positively correlated, they do not appear to significantly influence academic achievement, regardless of gender or academic track. The findings highlight the importance of fostering positive psychological attributes among students, though such factors alone may not directly predict academic success.